Impact of COVID‐19 on liver transplantation in Europe: alert from an early survey of European Liver and Intestine Transplantation Association and European Liver Transplant Registry. (13th August 2020) - Polak, Wojciech G.; Fondevila, Constantino; Karam, Vincent; Adam, Rene; Baumann, Ulrich; Germani, Giacomo; Nadalin, Silvio; Taimr, Pavel; Toso, Christian; Troisi, Roberto I.; Zieniewicz, Krzysztof; Belli, Luca S.; et al.
Summary: There are scarce data on the impact of COVID‐19 pandemic on liver transplantation (LT) in Europe. The aim of this study was to obtain a preliminary data on incidence, management, and outcome of COVID‐19 in liver transplant recipients and candidates in Europe. An Internet‐based survey was sent to the centers affiliated with European Liver Transplant Registry (ELTR). One hundred nine out of 149 (73%) of ELTR centers located in 28 European countries (93%) responded. Ninety‐four (86%) of the centers tested all donors, and 75 (69%) centers tested all LT recipients for SARS‐CoV‐2. Seventy‐three (67%) centers selected recipients for LT in the COVID‐19 pandemic, whereas 33% did not. Eighty‐eight centers reported COVID‐19 infection in 57 LT candidates and in 272 LT recipients. Overall crude incidence of COVID‐19 among LT candidates and recipients was estimated 1.05% (range 0.5–20%) and 0.34% (range 0.1–4.8%), respectively, and it was significantly higher among candidates ( P < 0.001). Crude rate of death was 18% (10/57) among candidates and 15% (36/244) among recipients. This first large‐scale European snapshot study clearly shows that both LT candidates and recipients are at a high risk for COVID‐19. These results plead for an early and pro‐active screening of COVID‐19 symptoms in these populations.